SUBTITUSI TEPUNG UBI JALAR DALAM PEMBUATAN BOLU GULUNG - Anton Ramadhan Ketra; Okta Wulandra (AGRITEPA: Jurnal Ilmu dan Teknologi Pertanian, 2015)
Making rollscakewithsweetpotatofloursubstitution hasbeen done.Thisstudyaimedto analyzethelevelofpanelistpreferenceforcolor,flavorandtextureofsweetpotatorollscake.Thisstudyusedavariationofthetreatmentformulationsflourand sweetpotatowiththreetreatments,iecomparisonofsweetpotatoflour:wheatflour750grams:250grams ;500grams:500grams;250grams:750grams.Parametersmeasuredwerepanelistspreferencelevelofthecolor,flavorandtexture.Theresultsshowedthatthesweetpotatoflourrollsinlikemostconsumersistheformulationofsweetpotatoflour500gramsand 500gramsofwheatflour.Keywords:rollscake,flour,sweetpotatoflour Making rolls cake with sweet potato flour substitution has been done . This study aimed toanalyze the level of panelist preference for color , flavor and texture of sweet potato rollscake. This study used a variation of the treatment formulations flour and sweet potato withthree treatments, ie comparison of sweet potato flour : wheat flour 750 grams : 250 grams; 500 grams : 500 grams ; 250 grams : 750 grams . Parameters measured were panelistspreference level of the color, flavor and texture . The results showed that the sweet potatoflour rolls in like most consumers is the formulation of sweet potato flour 500 grams and500 grams of wheat flour .Keywords : rolls cake , flour , sweet potato flour